Importance of Smart Monitoring Systems for Efficient Vacuum Sewer Performance and Modelling the Network - Ray Biswas, R (International Journal of Computer Sciences and Engineering, 2025)
A vacuum sewer system is one of the well-established alternative sewer technologies of modern times. The main objective of this study is to review the performance of vacuum sewer systems in post-earthquake Christchurch and assess the importance of real-time monitoring systems for the efficient and cost effective operation of a vacuum sewer network. The paper concludes that there are operational and cost benefits in installing smart monitoring systems across vacuum sewer networks. Modelling the operation of vacuum sewer systems correctly in a hydraulic modelling platform is important for hydraulic model building and calibration works. Modelling vacuum sewer systems poses a number of challenges such as the correct representation of differential pressure, modelling pressure interface valves, simulation runtime and stakeholders’ requirements. This paper highlights the different challenges when modelling vacuum sewer systems and summarises alternative methods that can be applied to model vacuum sewer networks.